Preliminary adipose removal did not prevent diet-induced metabolic disorders in mice. Issue 6 (20th March 2021) - Liu, Lin; Liang, Chen-Xi; Wang, Xiao-Wei; Pei, Ke-Xin; Ma, Xin-Di; Zhang, Chun-Xi; Dong, Jing-Hui; Gao, Ming-Ming; Liao, Jia-Wei
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Obesity is a fundamental factor in metabolic disorders such as hyperlipidemia, insulin resistance, fatty liver, and atherosclerosis. However, effective preventive measures are still lacking. This study aimed to investigate different surgical protocols for removing partial adipose tissue before the onset of obesity and determine whether, and by which protocol, preliminary adipose removal could exert potent preventive effects against diet-induced metabolic disorders. Methods: Male low-density lipoprotein receptor (LDL-R) knockout (KO) mice were randomly divided into four groups and subjected to epididymal fat removal (Epi-FR) surgery, subcutaneous fat removal (suQ-FR) surgery, both subcutaneous and epididymal fat removal (Epi + suQ-FR) surgery, or sham-operation. After 1 week of recovery, all mice were given a high-fat diet (HFD) for 10 weeks to induce metabolic disorders. Results: In the Epi-FR group and the sham-operated group, the mean numbers of the residual subcutaneous fat were 28.59 mg/g and 18.56 mg/g, respectively. The expression of relative genes such as Pparg, Cebpa, Dgat2, Fabp4 and Cd36 in the residual subcutaneous fat increased 2.62, 3.90, 3.11, 2.06, 1.78 times in the Epi-FR group compared with that in the sham-operated group. Whereas in the other fat-removal groups, the residual fat depots had no significant change in either size or gene expression, as compared with those of the sham-operated group. Plasma lipid and glucose levels and insulin sensitivity, as detected by the glucose tolerance test, were not significantly alleviated in the three fat removal groups. Liver mass or lipid content was not attenuated in any of the three fat removal groups. The atherosclerosis burdens in the entire inner aorta and aortic root did not decrease in any of the three fat removal groups. Conclusions: Our data suggest that removal of epididymal adipose or subcutaneous adipose alone or in combination before the onset of obesity did not protect against hyperlipidemia, insulin resistance, fatty liver, or atherosclerosis in LDL-R KO mice fed with a HFD. Hence, adipose removal possibly does not represent a potential approach in preventing obesity-related metabolic disorders in the obesity-susceptible population.